Assessment of Diversity and Distribution of Dominant Acrocarpous Moss Families in Pachmarhi Biosphere Reserve (Madhya Pradesh) - Nath, Virendra; Asthana, A. K.; Gupta, Reesa (Indian Forester, 2012)
Pachmarhi Biosphere Reserve (PBR), situated in Madhya Pradesh, India is well known for its biodiversity. Moss flora of the region is immensely significant considering the fact that mosses are abundantly found here. Most abundant families include Bryaceae (9), Pottiaceae (8), Dicranaceae (7) and Fissidentaceae (6) totaling 30 taxa. Interestingly, all the four moss families are acrocarpous indicating the dominance of erect mosses in the region. Further, Fissidens Hedw., Bryum Hedw., Campylopus Bridel. and Hyophila (Hook.) Jaeg. are the most abundant genera of these families. While Pottiaceae is dominant in terms of frequency of occurrence of its genera in different localities of PBR, Bryaceae shows maximum representation with 9 members. The mosses account for both epiphytic and terrestrial members and contribute substantially to the ecology and diversity of PBR.